+0  
 
0
352
2
avatar

sin^2(-x)+cos^2(-x)

Guest Mar 13, 2015

Best Answer 

 #2
avatar+19632 
+5

sin^2(-x)+cos^2(-x)

$$\boxed{
\begin{array}{ccc}
\sin(-x) &=& -\sin{x}\\
\cos(-x) &=& \cos(x)
\end{array}
}\\\\\\
\sin^2(-x)+\cos^2(-x)\\
=[-\sin(x)]^2+[cos(x)]^2\\
=\sin^2(x)+\cos^2(x)\\
=1$$

heureka  Mar 13, 2015
 #1
avatar+87301 
+5

sin^2(-x)+cos^2(-x)

Let -x  = θ

So

sin^2 (θ) + cos^2 (θ)  = 1   {this is just a basic identity}

 

  

CPhill  Mar 13, 2015
 #2
avatar+19632 
+5
Best Answer

sin^2(-x)+cos^2(-x)

$$\boxed{
\begin{array}{ccc}
\sin(-x) &=& -\sin{x}\\
\cos(-x) &=& \cos(x)
\end{array}
}\\\\\\
\sin^2(-x)+\cos^2(-x)\\
=[-\sin(x)]^2+[cos(x)]^2\\
=\sin^2(x)+\cos^2(x)\\
=1$$

heureka  Mar 13, 2015

6 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.